Using a deterministic matching computer routine to identify hospital episodes in a Brazilian de-identified administrative database for the analysis of obstetrics hospitalisations - Claudia Medina Coeli; Rosa Maria Soares Madeira Domingues; Lana Meijinhos; Daniela Medina Coeli Bastos; Rejane Sobrino Pinheiro; Valeria Saraceni; Marcos Augusto Bastos Dias; Natália Santana Paiva; Kenneth Camargo Jr (International Journal of Population Data Science)
Introduction The absence of a unique patient identifier in the Brazilian hospital administrative database prevents the identification of hospital episodes with multiple hospitalisations of the same patient.